Thermal Fatigue Properties of Ultrasonically Bonded Copper Joints - Takahito Fushimi; Yo Tanaka; Shinnosuke Soda; Tomoki Matsuda; Tomokazu Sano; Akio Hirose (Applied Sciences, 2019)
Thermal fatigue generally occurs in ultrasonically bonded copper joints in electronic devices as the bonding substrate is composed of plural materials, leading to differences in the coefficient of thermal expansion. In this study, we found that the thermal fatigue resistance of the ultrasonically bonded copper joints was influenced by the grain size and hardness of the bonding substrate through the evaluation of the thermal fatigue properties. Copper alloys C1020 and C1940 were used as substrate materials to investigate the influence of the initial properties of the bonding material on the thermal fatigue resistance. We evaluated the crack propagation due to thermal fatigue via thermal cycle tests. Microstructural observations of the region fractured because of thermal fatigue revealed that cracks resulting from thermal fatigue did not progress in the fine grain region formed at the bonded interface. It was inferred that grain boundaries were an obstacle to crack propagation. C1940 has higher hardness and finer grains than C1020, and showed a lower decreasing rate of the peel strength and bonding area after the thermal cycling test than C1020 joints. Thus, a hard copper material with fine grains is effective in suppressing thermal fatigue fracture of ultrasonically bonded copper joints.